2017
DOI: 10.1556/0806.45.2017.006
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced light intensity increases flavonol and anthocyanin concentrations but reduces flavone levels in the cotyledons of common buckwheat seedlings

Abstract: The effects of two light intensities on the concentration of several flavonoids were investigated in the cotyledons of common buckwheat seedlings. The study was performed on four days old seedlings of cvs. Hruszowska, Panda, Kora and Red Corolla. One group of seedlings was grown under exposure to 180 ± 20 μmol • m -2 • s -1 photosynthetically active radiation, whereas the other group was exposed to 360 ± 20 μmol • m -2 • s -1 . The experiment lasted 5 days. The results revealed that light intensity induces cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The seeds, sprouts and seedlings of both types of buckwheat contain a whole set of phenolic compounds, such as phenolic acids, flavonols, flavones, catechins, and anthocyanins [ 85 , 86 ]. Therefore, buckwheat seedlings are convenient objects for examining the impacts of environmental factors on these compounds [ 87 , 88 , 89 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seeds, sprouts and seedlings of both types of buckwheat contain a whole set of phenolic compounds, such as phenolic acids, flavonols, flavones, catechins, and anthocyanins [ 85 , 86 ]. Therefore, buckwheat seedlings are convenient objects for examining the impacts of environmental factors on these compounds [ 87 , 88 , 89 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that in F. tataricum , low temperature caused significant changes in the expression of histone deacetylases (HDACs) which correlated with flavonoid synthesis pathway genes [ 93 ]. Besides, when F. tataricum was subjected to cold stress, the anthocyanin content in the epidermis and cortex cells of the hypocotyl was twice as high as in the cotyledons increases their resistance to cold [ 91 ]. Moreover, metabolic profiling based on GC-TOF-MS analysis showed that most sugars and their derivatives increase significantly in response to cold [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, light can enhance several metabolites in certain plants as a physical factor [116][117][118] . In this respect, anthocyanins and flavones increased in response to high visible light levels 119 . Similarly, UV-B irradiation stimulates flavonoid synthesis by enhancing the phenylpropanoid pathway in Kalanchoe pinnata 120 .…”
Section: Enhancement Of Plant Nutraceuticals Production Bymentioning
confidence: 99%
“…Higher light intensity can increase anthocyanin accumulation in many plants [4,7]. Azuma et al (2012) showed that strong light may significantly induce anthocyanin accumulation in grape peel and simultaneously induce the high abundance expression of DFR, CHS, CHI, F3H, MT, F3'5'H, and GT [8].…”
Section: Introductionmentioning
confidence: 99%